The Ideological and Strategic Dimensions of American Support for Israel During the Gaza War - Chamas, Akram Mohammad Ali (Journal of Economic, Administrative and Legal Sciences, 2024)
The United States has provided comprehensive political, diplomatic, and military support to Israel to conduct a large-scale operation of genocide and ethnic cleansing in the Palestinian territories of Gaza, along with continued extreme violence in the West Bank and East Jerusalem. This operation began on October 7, 2023, resulting in the death and injury of tens of thousands of Palestinians, widespread destruction in Gaza, and the displacement of over a million Palestinians. Despite the ongoing massacres, the U.S. used its veto power in the Security Council against ceasefire resolutions, leading to the Council's failure to enact effective decisions The administration of President Joe Biden took a firm stance against the "Al-Aqsa Flood" operation carried out by Hamas on October 7, 2023, condemning it as a "terrorist" act and fully supporting Israel's "right to self-defense," pledging all necessary assistance. In a speech on October 10, Biden equated Hamas with al-Qaeda and ISIS, labeling it as "absolute evil." He praised Israel and highlighted the strong, over 50-year-long relationship between the U.S. and Israel, while omitting the suffering of Palestinians due to the extensive Israeli aggression on Gaza. He emphasized that Hamas does not defend the Palestinian people's right to dignity and self-determination.The aftermath of October 7 has raised two interconnected strategic issues: 1. The fate of Israeli existence: As a Western-American colonial project, Israel faces internal and external challenges threatening its stability. 2. The fate of American hegemony in the Middle East: American global influence in the region is at risk amidst a shifting world order towards multipolarity.
Keywords: Palestinian-Israeli Conflict; Al-Aqsa Flood; US Foreign Policy; War Crimes; Human Rights; Geopolitical Shift